Haematological outcome of concomitant chemoradiation with Temozolomide (CCRT) versus radiation therapy (RT) alone in patients with high grade gliomas - Rasheed, Md Mamun Or; Bhuiyan, Md Zillur Rahman; Sharmin, Sadia; Rahman, Atiar; Hossain, Md Monoar; Kader, Kazi Manzur (Bangladesh Medical Journal, 2017)
High grade gliomas(HGG) are the most common primary CNS tumors in adult. Even with multidisciplinary approach, the outcome is miserable. However recently concomitant chemoradiation (CCRT) with temozolomide has been effectively used with increase in median survival & good clinical outcome. This quasi experimental study was done in the department of Radiation Oncology in National Institute of Cancer Research & Hospital ( NICRH) Mohakhali , Dhaka during January 2014 to December 2014. Sixty patients with newly diagnosed & histologically proved high grade glioma were assigned to receive either radiation therapy alone (fractionated focal irradiation in daily fractions of 2 Gy in five fractions per week for six weeks, for a total 60 Gy) or radiation therapy plus Temozolomide( 75 mg/m2 from 1st day of radiation therapy to last day of radiation therapy) followed by six cycles of adjuvant temozolomide (150 to 200mg per square meter for five days during each 28 day cycle). Haematological abnormalities and neurotoxicities were compared between the patients of two arms. Patients treated CCRT showed more toxicities than the radiation therapy alone in some stages. As a whole the differences were not statistically significant. Bangladesh Med J. 2016 Sep; 45 (3): 126-130